ANALISIS PENDAPATAN DAN BREAK EVEN POINT (BEP) USAHATANI BAWANG MERAH DI DESA LAPANDEWA KAINDEA KECAMATAN LAPANDEWA KABUPATEN BUTON SELATAN - Mustari, La Ode Muhammad (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2018)
This study aims to determine how much the average income earned by farmers from shallot farming in Lapandewa Kaindea Village, Lapandewa Sub-district, South Buton Regency and how many Break Even Point (BEP) received by onion farmers in Lapandewa Kaindea Village, Lapandewa Sub-district, South Buton Regency. This study was carried out in Lapandewa Kaindea Village, Lapandewa Sub-district, South Buton Regency for two months from June to July 2017. The population of this research is the existing cashew farmers. The research sample was 32 cashew farmers. Data was collected through interviews using questionnaires and data analysis using cost and revenue analysis. The results showed that the average income earned by farmers in conducting onion farming activities with an area of ??0.1 - 0.25 ha, an average land area of ??0.14 ha with an average income of IDR 3.282.000, and a Break Even Point (BEP) IDR 1.541.000. Recommendations local governments, particularly at the district level need to establish regulations relating to the onion marketing system, especially the basic pricing.   Keywords: Income, Break Even Point (BEP), Onions